2012
DOI: 10.1128/aem.07308-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Scout Hypothesis and Microbial Discovery

Abstract: ABSTRACTIn this study, we examine the temporal pattern of colony appearance during cultivation experiments, and whether this pattern could inform on optimizing the process of microbial discovery. In a series of long-term cultivation experiments, we observed an expected gradual increase over time of the total number of microbial isolates, culminating in a 700-fold colony count increase at 18 months. Conventional thought suggests that long-term incubations result in a culture col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 29 publications
1
34
1
1
Order By: Relevance
“…OTU 19, an important shell bacterium found on affected shell, was most similar to other bacteria found in association with sponges (99% sequence identity, Sipkema et al 2011). It is likely that this bacterium is 52 Feinman et al: Bacterial communities in lobster shell disease from the genus Lutimonas (96% sequence identity, Buerger et al 2012), which is part of the same family as Aquimarina and may represent another opportunistic colonizer of diseased lobster shell.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…OTU 19, an important shell bacterium found on affected shell, was most similar to other bacteria found in association with sponges (99% sequence identity, Sipkema et al 2011). It is likely that this bacterium is 52 Feinman et al: Bacterial communities in lobster shell disease from the genus Lutimonas (96% sequence identity, Buerger et al 2012), which is part of the same family as Aquimarina and may represent another opportunistic colonizer of diseased lobster shell.…”
Section: Discussionmentioning
confidence: 89%
“…OTU 19, an important shell bacterium found on affected shell, was most similar to other bacteria found in association with sponges (99% sequence identity, Sipkema et al 2011). It is likely that this bacterium is 52 Feinman et al: Bacterial communities in lobster shell disease from the genus Lutimonas (96% sequence identity, Buerger et al 2012), which is part of the same family as Aquimarina and may represent another opportunistic colonizer of diseased lobster shell.In addition to these core microbiome members, which appear to be important due to their relative abundance on either the transitionary or affected shell, there were a number of other core microbiome OTUs that had identities similar to taxa identified in previous studies of epizootic shell disease. Several studies have reported Aquimarina 'homaria' as a potential causative agent in shell disease, including a bacterial challenge study that was able to recover this bacterium from lobsters with lesions (Quinn et al 2012a) and a next-generation sequencing study that examined healthy and diseased shell (Meres et al 2012).…”
mentioning
confidence: 89%
“…Epstein hypothesized that dormant bacteria (named scout) would awaken stochastically, without implications of external and environmental signals (152). If these hypotheses provided partially microbiological explanations, including the existence of viable but nonculturable cells (153), then extremely long-term incubations (Ͼ3 months) would not increase the proportion of new species isolation (154). The results of these experiments strongly suggest that the success in culturing of new species depends on the amount of cultivation effort rather than on the length of incubation.…”
Section: Signaling Compoundsmentioning
confidence: 99%
“…The results of these experiments strongly suggest that the success in culturing of new species depends on the amount of cultivation effort rather than on the length of incubation. Those authors concluded that the single-cell approach allows the recovery of many more colonies from the same inoculum, as does cultivation by dilution to extinction (154).…”
Section: Signaling Compoundsmentioning
confidence: 99%
“…Importantly, cultivability is not restricted to abundant species. The same techniques also capture many rare species (Buerger et al 2012, Shade et al 2012a. Still, only few cultivation studies make the effort to assess the abundance of isolated bacterial species in the field.…”
Section: Methodological Aspects For the Research Of Rare Bacterial Spmentioning
confidence: 99%